Anthracnose on Southern Highbush Blueberry - Douglas A Phillips; Maria C. Velez-Climent; Philip F. Harmon; Patricio R. Munoz (EDIS, 2018)
Information contained in this 4-page publication is intended for Florida blueberry growers to use as a guide in the identification of anthracnose, a group of fungal pathogens that affects a wide range of plants, including southern highbush blueberries (SHB). Written by Douglas A. Phillips, Maria C. Velez-Climent, Philip F. Harmon, and Patricio R. Munoz and published by the UF/IFAS Plant Pathology Department, May 2018. https://edis.ifas.ufl.edu/pp337